Effect of heat stress on blood parameter, carcass and meat quality of Black Bengal goat - Hashem, MA; Hossain, MM; Rana, MS; Hossain, MM; Islam, MS; Saha, NG (Bangladesh Journal of Animal Science, 2013)
The research was conducted to study the effect of heat stress on blood parameter, carcass characteristics and meat quality of the Black Bengal goat. Nine goats were randomly and equally divided into three groups having almost same age and weight. Three groups were divided as zero hour (T0), four hours (T4) and eight hours (T8) of heat exposure. The T0 group were not exposed to heat stress, the T4 and T8 group were exposed to heat by keeping them at outside for 4 (four) hours and 8 (eight) hours from 9.00 AM to 1.00 PM and from 9.00 AM to 5.00 PM, respectively. Temperaturehumidity index (THI) was calculated as 26.88 indicating all the experimental animals were in extreme severe heat stress. The blood parameter such as RBC, PCV%, Hb%, WBC was significantly (p<0.01) higher in T8 group than those of T4 and T0 groups. There was also significant (p<0.05) effect of heat stress on pH of the meat from different groups of the Black Bengal goats. By-products e.g., blood, pluck, spleen and kidney, and cooking loss were significantly (p<0.01) increased with the increase of the heat, but no significant differences were observed for pre-slaughter parameters, carcass weight, drip loss, dressing percentage, and proximate composition of the goat meat for DM, CP and Ash, while the EE significantly (p<0.05) differed among the heat treated groups. Heat stress significantly affected the blood parameter, cooking loss, pH, by-product of goats rather than non heat stressed group. It indicates that heat stress limits the qualitative and quantitative production characteristics of goat meat. DOI: http://dx.doi.org/10.3329/bjas.v42i1.15783 Bang. J. Anim. Sci. 2013. 42 (1): 57-61